Combating The Disinformation: Verifiying The Fact of Political Hoaxes in Election-2024 in Indonesia - Didik Haryadi Santoso; Rila Setyaningsih; Supadiyanto Supadiyanto (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2024)
The aim of this research is to identify and analyze disinformation as part of the hokas leading up to the 2024 elections in Indonesia, Besides this research aim to give the recommendation how to combating the disinformation. This study uses descriptive analysis techniques and is qualitative in nature. There are four (four) steps to the data analysis in this study. The first step is the data collection procedure using web crawlers, data reduction comes in second, third, the method for displaying data. Data visualization is done methodically to facilitate analysis and conclusion drawing. This research has been able to identify and analyze the emergence of hoaxes ahead of the 2024 election. During the period 19 July-25 October 2023 there were 21 hoaxes about manipulated content, 3 hoaxes about defamation and reputation damage, and 2 hoaxes about emotional provocation tactics. Verifying the fact as the combating the disinformation ahead of the 2024 Presidential Election could be conducted by news verification techniques, including: (1) checking the source; (2) checking the facts; (3) checking the images; and (4) checking the date.